Intelectualidade e poder: uma antropologia política da Revista Brasileira de Mercado de Capitais - Almeida, Gabriel Henrique Lino de (Universidade Federal de São Carlos, 2025)
This dissertation examines the political and academic activities of an elite group that played a decisive role in shaping the Brazilian capital market—particularly through conducting research and proposing guidelines for the regulation and management of this key sector of the economy. The main object of analysis is the Revista Brasileira de Mercado de Capitais (Rbmec), a scholarly journal devoted to the study of the capital market and published between 1974 and 1996. Edited by the now-defunct Instituto Brasileiro de Mercado de Capitais (IBMEC), the journal became renowned for its pioneering role in fostering academic debates on the capital market in Brazil. The study begins by tracing the connections between IBMEC and a network of institutions that provided the intellectual foundation and financial and political support for the 1964 civil-military coup. It then turns to an in-depth exploration of the journal’s publications, with particular emphasis on discussions surrounding capital market regulation and the role of the State as a player within the financial industry. Adopting a political anthropology of finance approach, the dissertation situates these debates within a broader global historical framework. By doing so, it seeks to uncover the intellectual and political connections that reveal how the financial industry produces and sustains hierarchies on a global scale—thereby avoiding the trap of merely reproducing the terms and perspectives used by the financial capital itself.
Intellectuality and power: a political anthropology of the Revista Brasileira de Mercado de Capitais (Brazilian Journal of Capital Markets)
Keywords: Revista Brasileira de Mercado de Capitais; Instituto Brasileiro de Mercado de Capitais; Antropologia das finanças; Antropologia política; CIENCIAS HUMANAS::ANTROPOLOGIA::ANTROPOLOGIA URBANA; 10. Redução das Desigualdades; 16. Paz, Justiça e Instituições Eficazes; 4. Educação de Qualidade